Desenvolvimento de sistema computacional integrado de dimensionamento e representação gráfica de canais de macrodrenagem - MARTINS, Vania Carla Dias (Universidade Federal do Pará, 2023)
Develops an integrated computer system for the design and graphic representation of macrodrainage channels, including the hydrological, hydraulic, hydrodynamic design steps and graphic design elements. The system conceived and named SIDCAM was developed with a central model built in Java (MACRO 1.0), which is integrated with three external software, Google Earth, HEC-RAS and AutoCAD. For this, the research was carried out in three stages: (1) identification of methods and software, necessary for the development of a macrodrainage project; (2) development of the software in Java, for the hydrological and hydraulic design stages (phase 1), and, development of tools for integration, import and export of data, between the hydraulic module and the HEC-RAS and AutoCAD software (3 ) evaluation of the functionality and reliability of SIDCAM, through its application in the case study of the macrodrainage project of Tucunduba, Belém/PA. SIDCAM is composed of four modules: the hydrological module, for the generation of hyetograms and project hydrographs, using the alternating blocks and triangular hydrograph (SCS) methods; the hydraulic module, for making the geometric design of the channel and the coincidence of flow peaks with high tide peaks; the hydrodynamic module, to validate the SIDCAM geometric design; and the graphic module, for the automatic production of editable graphic pieces, of longitudinal and transverse profiles. In addition to the modules, import directories of IDF and tide gauge curves were built, fed by two databases, for IDF coefficients of 165 Brazilian municipalities and tide gauge curves of 334 stations of the Brazilian Navy. In the analysis of the water levels in the channel, simulated by the developed system, most of the results were classified as “Good” and “Very Good”, with Nash-Sutcliffe coefficients greater than 0.97, a minimum percentage error of 1.19% and a maximum of 14.72%. In view of these results, the proposed tool is promising, especially because it is a model that concentrates a good part of the processes necessary for a macrodrainage project, in a single integrated structure, thus filling gaps left by current models, which have a dissociative approach to the different stages of the project.